Integrating environmental sustainability and social justice principles into South Africa's blue economy initiative: re-imagining the political economy of our ocean - Sowman, Merle; Sunde, Jackie (Frontiers in Ocean Sustainability, 2024)
South Africa has vigorously embraced the concept of the blue economy. However, the scope, scale and impacts of South Africa's blue economy initiative, have raised significant concerns amongst local communities, NGOs and scholar activists in South Africa who are challenging South Africa's conceptualization of, and approach to “blue growth.” This paper provides a critique of South Africa's approach to planning, developing and governing the ocean economy and argues that the principles of social justice and environmental sustainability have been sidelined in favor of pursuing rapid economic growth. The paper examines key issues in the literature, environmental assessment processes, various legal cases that deal with mining, oil and gas applications, as well as insights from participation in several workshops with small-scale coastal fishing communities where issues on the blue economy were explored. These issues are discussed in relation to the growing literature on inclusive governance and integration of social justice and equity principles as foundational for fostering a sustainable and equitable blue economy. We conclude with proposals for embedding environmental sustainability and social justice principles, in a co-created blue economy policy and governance framework for South Africa.